Pengembangan Dan Implementasi Perangkat Pembelajaran Kimia SMA Model Pembelajaran Berbasis Portofolio Untuk Menunjang Pelaksanaan Kurikulum Berbasis Kompetensi - Holiwarni, Betty (Jurnal Pilar Sains, 2008)
The development of instructional tool is based on not availability of material resources for applyingcompetency based curriculum proferly. In this research, it has been developed chemistry lesson tools, such asPeriodical system and Atomic Structure for Portofolio learning´s Model. Instructional tools validator iscarried out by validator who has knowledgeable/ experts on instructional models and chemistry lesson,whileous to over viewed/ observed the effectivity and runny well of instructional tools. It has beenimplemented all activities in class experiment. The instructional tools developed sylaby, insructional plan,student activity sheets, Evaluation sheets. The development instructional tools is based on Thiagarajan´sDesign, sammel and Sammel (1974). The model consists 4 stages and is well know as four-D Models. Theimplementation of chemical instructional tools has breen running in class with classroom action researchwhile subjeck orf this research is MAN 2 Pekanbaru. The result of research conclusison is instructional tools,Validation and implemantation in class shows the instructional tools of portofolio model is valid, practicaland effective to support competency based curriculum in learning process.Key word : Model Pembelajaran Portofolio, Kurikulum Berbasis Kompetensi